Analysis and evaluation of a practical downlink multiuser MIMO scheduler over LTE advanced massive MIMO systems - Arnott, Rob; Oketani, Kengo; Prasad, Narayan; Rangarajan, Sampath; Wells, Patricia (2016 50th Asilomar Conference on Signals, Systems and Computers, 2016)
In this paper, we construct and comprehensively analyze a practical downlink (DL) multiuser (MU) multi-input-multi-output (MIMO) scheduling algorithm over LTE Advanced (LTE-A) massive MIMO cellular networks. We first design an efficient approximation algorithm to maximize the weighted sum rate subject to certain mandatory practical constraints, and prove that our algorithm can yield a meaningful approximation guarantee. We then process the obtained scheduling decision to obtain one that is fully compliant with the LTE-A standard. Comprehensive system level evaluation is conducted by emulating an LTE-A massive MIMO network and potential gains are demonstrated.